Effects of Micro-Laboratory Demonstration Activities on Science Engagement and Mastery Towards Learning Flow - Panergayo, Albert Andry; Ate, Cyrell; Gregana, Clarissa (Jurnal Pendidikan IPA Indonesia, 2026)
Science mastery and engagement remain a persistent challenge in Philippine public schools, often due to limited access to laboratory resources and passive instructional methods. In view of this, the study designed and implemented Micro-laboratory Demonstration Activities (MLDAs) that are cognitively enriching, emotionally immersive, and behaviorally engaging. The MLDAs aim to unlock learning flow through hands-on tasks with clear objectives, appropriate challenges, and immediate feedback. Using educational action research, five expert-validated activities were designed to promote science mastery and engagement, achieving a strong content validity (S-CVI > 0.90) and high reliability (α=0.89), were designed to promote science mastery and engagement (α=0.89). The researchers administered the designed MLDAs to a sample of Grade 8 struggling students (n=42). Paired-sample t-tests revealed statistically significant improvements across all cognitive domains of science mastery, with large effect sizes in remembering (d=0.83), applying (d=0.95), analyzing (d=1.03), and overall mastery (d=1.51), while understanding showed a medium effect (d=0.74). The survey, observational data, and student interviews confirmed sustained high student engagement. Thematic analysis identified five prominent themes in students' perspectives and experiences regarding MLDAs: hands-on learning, collaborative play, sensory appeal, conceptual clarity, and creative facilitation. These findings show that MLDAs are effective tools for fostering higher-order thinking, sustained engagement, and transformative science learning in resource-constrained classrooms.